The Impact of Climate Change on Ocean Submesoscale Activity. Issue 5 (29th April 2021) - Richards, K. J.; Whitt, D. B.; Brett, G.; Bryan, F. O.; Feloy, K.; Long, M. C.
Abstract: Global warming may modify submesoscale activity in the ocean through changes in the mixed layer depth (MLD) and lateral buoyancy gradients. As a case study we consider a region in the NE Atlantic under present and future climate conditions, using a time‐slice method and global and nested regional ocean models. The high resolution regional model reproduces the strong seasonal cycle in submesoscale activity observed under present‐day conditions. Focusing on the well‐resolved winter months, in the future, with a reduction in the MLD, there is a substantial reduction in submesoscale activity, an associated decrease in kinetic energy (KE) at the mesoscale, and the vertical buoyancy flux induced by submesoscale activity is reduced by a factor of 2. When submesoscale activity is suppressed, by increasing the parameterized lateral mixing in the model, the climate change induces a larger reduction in winter MLDs while there is less of a change in KE at the mesoscale. A scaling for the vertical buoyancy flux proposed by (Fox‐Kemper et al., 2008; doi:10.1175/2007JPO3792.1) based on the properties of mixed layer instability (MLI), is found to capture much of the seasonal and future changes to the flux in terms of regional averages as well as the spatial structure, although it over predicts the reduction in the flux in the winter months. The vertical buoyancy flux when the mixed layer is relatively shallow is significantly greater than that given by the scaling based on MLI, suggesting during these times other processes (besides MLI) may dominate submesoscale buoyancy fluxes. Plain Language Summary: The physical structure of the upper ocean is an important control on ocean‐atmosphere exchange of momentum, heat, freshwater, and gases such as carbon dioxide. It also regulates the distribution of nutrients and their delivery to the sunlit upper ocean, thereby impacting biological production. Processes occurring at horizontal scales of 1–10 km (the so‐called submesoscale) play an important role in structuring the upper ocean. This study considers how these processes may change under global warming. We find, associated with a warming of the upper ocean, a significant decrease in submesoscale activity and a reduction in the associated vertical flux of heat. Our results strongly suggest changes at these scales and their impact on the upper ocean need to be taken into account when assessing the impact of global warming. Key Points: Submesoscale activity is substantially reduced under global warming A scaling for the vertical buoyancy flux based on mixed layer instability overestimates the reduction in the flux under global warming The reduction in mixed depth under global warming is reduced when submescale activity is included